Mapping organizational culture in the hospital setting - Gabriel, Elena; Middleton, Nicos; Papastavrou, Evridiki; Merkouris, Anastasios (My University, 2017)
Organizational culture determines what people should say and do, and generally the usual way of doing things in a specific organization. Its description is one of the many ways to assist in understanding an organization. This is a review of the organizational culture in the hospital setting, its correlation with indicators of effectiveness, and identification of possible associated factors. A literature search was conducted in the electronic databases PubMed, CI-NAHL, Academic Search Complete and EMBASE for articles published from 2000 onwards. Analysis of the 31 reports included in the review showed that the prevailing organizational culture in hospitals is the hierarchical/bureaucratic, followed by the group/human relations culture. The hierarchical/bureaucratic type of culture was found to be negatively correlated with most of the effectiveness indicators investigated, including patient satisfaction, job satisfaction, job safety, changes in attitude, group relations, education, etc. In contrast, the group/human relations type of culture was associated positively with indicators such as patient satisfaction and safety, clinical outcome, infection prevention, overall quality management, change, collaboration, learning, profitability, job satisfaction and commitment, etc. Some culture types, such as the innovative/developmental culture, were associated positively with effectiveness indicators, whereas others, such as the rational/market culture, were negatively associated with a smaller number of effectiveness indicators. Some studies reported that factors influencing the organizational culture were the ownership status of hospitals (public/private) and the demographic features of the staff surveyed (profession, position in hierarchy, years of service, age and gender). Hospital administrations should aim to strengthen the group/ human relations type of culture, which has been shown to promote performance indicators. © Athens Medical Society.
Keywords: Effectiveness indicators; Hospital; Organizational culture